Planktonic Foraminifera Biozonation of the Middle Eocene-Oligocene Kebo Formation, Kalinampu Area, Bayat, Klaten, Central Java - Dian Novita; Didit Hadi Barianto; Moch. Indra Novian (Berita Sedimentologi, 2014)
Research on foraminifera from the Paleogene volcanoclastics-dominated Kebo Butak Formation of Central Java is limited. A study was conducted in the Kalinampu and surrounding areas of Bayat, Klaten, Central Java. The study included measuring of three stratigraphic sections and geological mapping. The study area contains the Nampurejo pillow lava, which is considered to be the base of the Kebo-Butak Formation (part of the 'Old Andesites' complex of South Java), but its Middle Eocene age is older than previously assumed.Correlation and biozone interpretation allowed the recognition of 12 planktonic foraminifera zones, ranging in age from Middle Eocene (P11) to Early Miocene (N5). Depositional environments are all deep marine, ranging from lower bathyal to upper bathyal.